New approach methods to improve human health risk assessment of thyroid hormone system disruption–a PARC project - Ramhøj, Louise; Axelstad, Marta; Baert, Yoni; Cañas-Portilla, Ana I.; Chalmel, Frédéric; Dahmen, Lars; De La Vieja, Antonio; Evrard, Bertrand; Haigis, Ann-Cathrin; Hamers, Timo; Heikamp, Kim; Holbech, Henrik; et al. (Frontiers in Toxicology, 2023)
Current test strategies to identify thyroid hormone (TH) system disruptors are inadequate for conducting robust chemical risk assessment required for regulation. The tests rely heavily on histopathological changes in rodent thyroid glands or measuring changes in systemic TH levels, but they lack specific new approach methodologies (NAMs) that can adequately detect TH-mediated effects. Such alternative test methods are needed to infer a causal relationship between molecular initiating events and adverse outcomes such as perturbed brain development. Although some NAMs that are relevant for TH system disruption are available–and are currently in the process of regulatory validation–there is still a need to develop more extensive alternative test batteries to cover the range of potential key events along the causal pathway between initial chemical disruption and adverse outcomes in humans. This project, funded under the Partnership for the Assessment of Risk from Chemicals (PARC) initiative, aims to facilitate the development of NAMs that are specific for TH system disruption by characterizing in vivo mechanisms of action that can be targeted by in embryo/in vitro/in silico/in chemico testing strategies. We will develop and improve human-relevant in vitro test systems to capture effects on important areas of the TH system. Furthermore, we will elaborate on important species differences in TH system disruption by incorporating non-mammalian vertebrate test species alongside classical laboratory rat species and human-derived in vitro assays.